Conservação de plantas medicinais no entorno do Parque Nacional de Sete Cidades, Piauí, Brasil - Ferreira, Ezequiel da Costa (2023)
The use of medicinal plants is an ancient practice among human populations and essential for primary health care, especially in less developed countries or regions. Several species of medicinal plants may be under threat due to several factors such as excessive extractivism, habitat loss and climate change. In this context, this study aimed to evaluate the conservation priorities and the impacts of climate change on medicinal plant species used in the Cachoeira rural community, around the Sete Cidades National Park, in the state of Piauí, Northeastern Brazil, in addition to compare various quantitative indices of ethnobotany in order to assess whether there is a correlation between the different indices. Data collection on the medicinal plants used was carried out through semi-structured interviews applied to the heads of families in the studied community, with 27 community residents (13 men and 14 women) being interviewed. Based on the data obtained in the interviews, a phytosociological inventory was carried out using the quadrant point method, in order to identify the species cited by residents in the local vegetation. The analysis of the phytosociological data was carried out by adopting the parameters of Relative Density, Relative Frequency, and Relative Dominance. To assess the cultural importance of each species used, data from the interviews were analyzed using eight different quantitative methods and correlated with each other using Pearson's Correlation Coefficient, using the Bioestat 5.0 Program. To establish the priority species for conservation, the calculation of the Conservation Priority Index (CPI) was used. In order to evaluate the pressure of use that each species suffers, the Indication of Pressure by Preference of Use of Species (IPPU) was applied. Data on species distribution were also collected. 24 species of medicinal plants were identified, belonging to 15 families, with Fabaceae and Anacardiaceae being the most expressive in number of species. Only 12 species mentioned in the interviews were sampled in the vegetation, of which seven had a high priority for conservation, a worrying fact that may indicate that there is strong pressure to use medicinal plants in the region. Among the species used, those that obtained the highest values among the cultural indices analyzed were Ximenia americana, Amburana cearensis, Myracrodruon urundeuva, Cariocar cuneatum, Terminalia argentea and Anadenanthera colubrina. A strong correlation was observed, in general, between the cultural indices analyzed among themselves. Of the 12 species sampled in phytosociology, 7 had high conservation priority. It is notable that Ximenia americana stands out among all cultural importance indices, at the same time that it is presented as the species with the highest Conservation Priority, given that a careful look at the conservation of this species is necessary.